Expertise: Forecasts of EU Cohesion Policy Impact on Regional Economies of Lubelskie and Podkarpackie Voivodships till the Year 2015 - Zaleski, Janusz; Tomaszewski, Paweł; Zembaty, Marek (Regional Barometer. Analyses & Prognoses, 2008)
Authors presented historical data and forecasts of the macroeconomic performance of the two regional economies: lubelskie and podkarpackie. Projected values of a set of basic macroeconomic parameters (rate of GDP growth, level of GDP by PPS with reference to EU-27 average, unemployment rate) are presented till the year 2015. Special attention was paid to evaluation of EU cohesion policy macroeconomic impact on selected variables (rate of GDP growth, level of GDP by PPS with reference to EU-27 average, unemployment rate, employment). Simulations were made using the regional HERMIN models for the two voivodships. National and regional adaptations of the HERMIN macroeconomic model were built in Poland in the years 2002-2005 and since then are systematically developed by the Wroclaw Regional Development Agency team headed by Prof. Janusz Zaleski of the Wroclaw Technical University in co-operation with by Dr. John Bradley of the Economic and Social Research Institute (Dublin, Ireland) – an author of the original HERMIN model for the Irish Economy.